Review of small farmer access to agricultural credit in Nigeria - Badiru, Idris Olabode (International Food Policy Research Institute, 2010)
The important role of credit in agricultural enterprise development and sustainability has prompted the Federal Government of Nigeria (FGN) to establish credit schemes such as the Agricultural Credit Guarantee Scheme (ACGS) and Agricultural Credit Support Scheme (ACSS) to ensure farmers' access to agricultural credit. Yet, the situation has not improved substantially; based on the 2006 Core Welfare Indicators Questionnaire Survey, it is estimated that only 18 percent of farm households (mainly smallscale farmers) have access to financial services (Akramov 2009). This brief reviews existing knowledge on small-scale farmers' access to credit with particular focus on conditions for accessing credit, the maximum credit provided, repayment of credit, other factors limiting access, and the impact of credit on small-scale farmers.